2019
DOI: 10.1177/1833358319855031
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative evaluation of clinically coded data quality from health information manager perspectives

Abstract: Background: It is essential that clinical documentation and clinical coding be of high quality for the production of healthcare data. Objective: This study assessed qualitatively the strengths and barriers regarding clinical coding quality from the perspective of health information managers. Method: Ten health information managers and clinical coding quality coordinators who oversee clinical coders (CCs) were identified and recruited from nine provinces across Canada. Semi-structured interviews were conducted,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 18 publications
0
44
0
Order By: Relevance
“…Although it is a reasonable assumption that clinical coder experience is associated with our misclassification estimates, in the setting of IFI where clinical case definitions are complex, it is conceivable that other factors are at play. This includes the complexity of translating clinical data indicating invasive aspergillosis into ICD-10-AM [ 24 , 26 ], the absence of clear definitions [ 27 , 28 ], subjective interpretation of existing guidelines [ 24 , 25 , 27 ], delays in diagnosis [ 29 ], and the review of multiple data sources to make a confirmatory diagnosis of mould infection [ 1 , 2 , 30 ]. This setting underscores the importance of clear, complete, legible and standardised documentation of IFI to mitigate misclassification in current coding workflows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although it is a reasonable assumption that clinical coder experience is associated with our misclassification estimates, in the setting of IFI where clinical case definitions are complex, it is conceivable that other factors are at play. This includes the complexity of translating clinical data indicating invasive aspergillosis into ICD-10-AM [ 24 , 26 ], the absence of clear definitions [ 27 , 28 ], subjective interpretation of existing guidelines [ 24 , 25 , 27 ], delays in diagnosis [ 29 ], and the review of multiple data sources to make a confirmatory diagnosis of mould infection [ 1 , 2 , 30 ]. This setting underscores the importance of clear, complete, legible and standardised documentation of IFI to mitigate misclassification in current coding workflows.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of invasive aspergillosis cases in the gold-standard data were small (N = 15), our findings are likely indicative of the uncertainty in discriminating between yeast and mould infections at the clinical coding level. A recent qualitative study [25] identified clinical coders' experience and awareness of IFI as a factor associated with discordant coding. Although it is a reasonable assumption that clinical coder experience is associated with our misclassification estimates, in the setting of IFI where clinical case definitions are complex, it is conceivable that other factors are at play.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Methods to assess the quality differed across studies. One approach to assessing quality involved focus groups and interviews of Health Information Managers and coders [1,2]. This qualitative research found problems in completeness, accuracy, and consistency in coding.…”
Section: Quality Of Ehr Datamentioning
confidence: 99%
“…The inpatient database relies heavily on electronic inpatient documents (specifically the discharge summaries). When the discharge summary (DS) is unavailable electronically, trained coders use the paper DS, which often presents challenges in discerning illegible handwriting for the presence of codable diagnoses [4]. As a result, many healthcare facilities are transitioning to a fully electronicbased documentation system [5].…”
Section: Introductionmentioning
confidence: 99%